Influence of hydrogel aging temperature in the formation of mesoporous molecular sieve MCM-48 - Oliveira, T. G.; Pedrosa, A. M. G.; Souza, M. J. B. (Scientia Plena, 2012)
Using two temperatures different of synthesis, 120°C and 150°C, mesoporous molecular sieve MCM-48 were hydrothermally synthesized. To investigate the effect of temperature on the structure properties of materials denoted as MCM-48/120 and MCM-48/150 were characterized by X-ray diffraction (XRD), N2 adsorption-desorption and thermogravimetric analysis (TGA). Both samples resulted in cubic phase MCM-48, however the material synthesized at higher temperature showed better texturais characteristics as the highest surface area, pores volume and size.